Almost at the top, but not quite: Senior management's sources of power and their influence on HRM - Mirfakhar, A.; Jordi Trullen; Mireia Valverde (Research Handbook on Line Managers, 2022)
The role of senior managers, understood as those sitting at the apex of the organizational hierarchy in charge of strategic decisions (e.g. CEOs, VPs, etc.) but still dependent on a higher authority, has so far been little explored in the HRM process literature. Yet, senior managers exert a large influence on middle and front line managers, who are key actors in the translation of HRM strategy into HRM outcomes. Using a comparative case study, we adopt a power perspective to show the different ways in which senior managers use different sources of power to shape HRM in their organizations, while also recognizing the influence exerted by other internal (at upper and lower levels) and external (e.g. key customers or suppliers) actors with whom they interact. The chapter contributes in this way to the small but growing research stream on the role of top management in HRM.